2006
DOI: 10.1021/ja0623663
|View full text |Cite
|
Sign up to set email alerts
|

Azide Reactions for Controlling Clean Silicon Surface Chemistry:  Benzylazide on Si(100)-2 × 1

Abstract: A combination of experimental and computational studies presents direct proof of a novel reaction pathway that delivers aromatic compounds onto a Si(100)-2 x 1 substrate. Benzylazide chemisorbs on a Si(100)-2 x 1 surface, and this chemisorption is followed by nitrogen elimination, leading to a stable surface adduct based on a Si-Si-N cyclic entity. This reaction occurs via a stable surface intermediate with the surface-bound nitrogen molecule stabilized by the presence of a neighboring aromatic group, which ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 8 publications
3
43
0
Order By: Relevance
“…Figure reprinted with permission from Ref. [165]. c 2007, American Chemical Society the possibility of oxygen contamination is eliminated.…”
Section: Functionalized Aromaticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure reprinted with permission from Ref. [165]. c 2007, American Chemical Society the possibility of oxygen contamination is eliminated.…”
Section: Functionalized Aromaticsmentioning
confidence: 99%
“…The experimental studies of this proposal have been complicated by the fact the phenylazide (Ph-N 3 ) is explosive under distillation conditions, the very conditions needed for its introduction into the vacuum system. Nevertheless, a close homologue of phenylazide, azidobenzene (Ph-CH 2 -N 3 ), which is more stable and commercially readily available, has indeed been investigated [165]. The final product of the azidobenzene reaction with the Si(100)-2×1 surface was confirmed to be the three-member Si-N-Si ring [165], while the experimental studies also confirmed the 1,2-cycloaddition with the formation of an adduct similar to the phenyl isothiocyanate [215], rather than the fivemember Si-N-N-N-Si ring predicted theoretically [164].…”
Section: Functionalized Aromaticsmentioning
confidence: 99%
“…It is now possible to form monolayers with various linking groups, including SiÀC, SiÀO, and SiÀN. [14][15][16] Among them, the formation of SiÀC-bound organic layers through hydrosilylation on the hydrogen-terminated silicon (henceforth referred to as Si À H) substrate has been the most intensively studied. The Si À C bond can be formed with or without radical initiators through thermal treatment, [17,18] photochemical methods, [19,20] or utilizing Lewis acid catalysts.…”
Section: Si à C-bound Organic Monolayers and Their Functionalizationmentioning
confidence: 99%
“…The mechanisms of most of the addition processes are often described in these terms. For example, in a Diels-Alder reaction with butadiene, the dimers at the Sið100Þ-2 × 1 and Geð100Þ-2 × 1 surfaces were considered the dienophile (16-18) and other pericyclic reactions on both clean Si and Ge surfaces are described in a similar manner (19)(20)(21).In the current work, we extend this idea of describing the reactive surface moieties through their defined electrophilic or nucleophilic properties to the adsorbate species themselves. By taking the same approach for functionalized surfaces, we add to our ability to fine tune many chemical processes by selecting similar functionalities that exhibit different reactivities.…”
mentioning
confidence: 99%
“…The mechanisms of most of the addition processes are often described in these terms. For example, in a Diels-Alder reaction with butadiene, the dimers at the Sið100Þ-2 × 1 and Geð100Þ-2 × 1 surfaces were considered the dienophile (16)(17)(18) and other pericyclic reactions on both clean Si and Ge surfaces are described in a similar manner (19)(20)(21).…”
mentioning
confidence: 99%